Altered Ecosystems - Rosales, Judith (Delve Publishing, 2020)
Altered Ecosystems talks about the ecosystem, biodiversity and ecological alterations, the ecological relationship between water and soil. It further comprises the major causes of biodiversity loss, wildlife responses to modified natural habitats and change in soil, streams and rivers. This book also discusses about measures of biodiversity conservation, human and disturbance ecology, alterations caused to health of humans by disturbances and migration of humans and its subsequent effects on ecological disturbances. It also provides the reader with the basic concept of ecosystem and biodiversity in order to analyze the relationship between water and soil and recognize the causes of biodiversity loss and responses of wildlife to the altered natural habitats.